EFEKTIVITAS PENGGUNAAN VIDIO DAN GAME PUZZLE MAKER DALAM MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN FIQIH MATERI PUASA - Jasiah, Jasiah; Dedy Suhada (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to analyze the effectiveness of using video media and the Puzzle Maker game in increasing students' learning motivation in Fiqh subjects, especially fasting material, using the PPE (Planning, Production, Evaluation) method. At the planning stage, a learning needs analysis was carried out through interviews with teachers, classroom observations, and collecting initial data about student learning motivation at Darul Ulum Palangka Raya Middle School. The production stage involves developing media in the form of learning videos that are relevant to the fasting material and designing an interactive Puzzle Maker game. The evaluation stage includes the implementation of learning media for class IX students, followed by evaluation using learning motivation questionnaires, observations and interviews. The research results show that the combination of video media and the Puzzle Maker game significantly increases students' learning motivation compared to conventional learning methods. Video media helps students understand the material more clearly through visualization, while the Puzzle Maker game increases students' active involvement and memory of the material. Student responses were very positive, with the majority stating that learning had become more interesting and enjoyable. Challenges faced in this research include limited time for preparation and technical obstacles in accessing technological devices. Based on the research results, it can be concluded that the PPE method using video media and the Puzzle Maker game is an effective innovative learning strategy for increasing students' learning motivation in Fiqh subjects at Darul Ulum Palangka Raya Middle School. This research recommends implementing a similar method with adjustments to students' conditions and needs for more optimal results.